New insights into the protective effect of statherin-derived peptide for different acquired enamel pellicle formation times on the native human enamel surfaces. (April 2023) - Ventura, Talita Mendes Oliveira; Buzalaf, Marília Afonso Rabelo; Baumann, Tommy; Pelá, Vinícius Taioqui; Niemeyer, Samira Helena; Crusca, Edson; Marchetto, Reinaldo; Lussi, Adrian; Carvalho, Thiago Saads
Abstract: Objectives: This study evaluated the protective impact of acquired enamel pellicle (AEP) engineering with statherin-derived peptide (StatpSpS), considering different AEP formation times. Design : A total of 120 native human enamel specimens were divided into 2 main groups: 1) No AEP engineering and 2) AEP engineering with StatpSpS (pretreatment for 1 min; 37 °C, under agitation). Each group was further divided into 4 subgroups: No pellicle, or 1, 60-and-120 min AEP formation times (human saliva; 37 °C). The specimens were then subjected to an erosive challenge (1% citric acid; pH 3.6; 1 min; 25 °C). This procedure was repeated for 5 cycles. Relative surface reflection intensity (%SRI) was measured and scanning electron microscopy (SEM) of the enamel surface was done. Results : All AEP engineering groups protected against initial dental erosion in comparison with No pellicle (p < 0.001), likewise all groups with AEP, independent of engineering or formation times (p 0.001). Furthermore, engineering with StatpSpS even without the presence of AEP protected the enamel when compared to the No engineering/No pellicle group (p < 0.0001). No difference was observed regarding the protection from the different AEP formation times (p > 0.05). Regarding the SEM analysis, in the "No AEP engineering & No AEP" group, a more severe effect of citric acid was observed, with more enamel prism heads and scratches on the surface when compared with the other groups. Conclusions: AEP provides almost instant protection at formation times even as short as 1 min, protecting the native enamel against erosion. Treatment with StatpSpS by itself provides similar protection as the AEP. Graphical Abstract: ga1 Highlights: Acquired enamel pellicle provides almost instant protection of the native enamel. Statherin-derived peptide by itself provides similar protection as the pellicle. Hypothesis of the action mechanism of the StatpSpS on pellicle engineering. Our data suggest reducing pellicle formation times in future in vitro studies.